Enhancement of sorghum grain yield and nutrition: A role for arbuscular mycorrhizal fungi regardless of soil phosphorus availability. Issue 2 (14th October 2021) - Watts‐Williams, Stephanie J.; Gill, Alison R.; Jewell, Nathaniel; Brien, Christopher J.; Berger, Bettina; Tran, Binh T. T.; Mace, Emma; Cruickshank, Alan W.; Jordan, David R.; Garnett, Trevor; Cavagnaro, Timothy R.
Societal Impact Statement: Sorghum is an important cereal crop that provides calories and nutrients for much of the world's population, and it is often grown with low fertiliser input. Optimising the yield, nutritive content and bioavailability of sorghum grain with minimal input is of importance for human nutrition, and arbuscular mycorrhizal (AM) fungi have previously shown potential to assist in this. Across sorghum genetic diversity, AM fungi improved the yield, nutrition and zinc and iron bioavailability of grain in a low phosphorus soil. Thus, food production systems that effectively manage AM fungi may improve consumer outcomes. Summary: Sorghum is a C4 cereal crop that is an important source of calories and nutrition across the world, predominantly cultivated and consumed in low‐ and middle‐income countries. Sorghum can be highly colonised by arbuscular mycorrhizal (AM) fungi, and the plant‐fungal association can lead to improvements in biomass and nutrient uptake. High‐throughput phenotyping allows us to non‐destructively interrogate the 'hidden' effects of AM fungi on sorghum growth and phenology. Eight genetically diverse sorghum genotypes were grown in a soil amended with 2 or 20 mg P kg −1 and inoculated with an AM fungal culture of Rhizophagus irregularis . High‐throughput phenotyping uncovered the 'hidden' effects of AM fungi on growth and phenology, while grain biomass, nutrition, Zn and Fe bioavailability and root AM colonisation was determined after destructive harvest. Sorghum plants colonised by AM fungi generally performed better than non‐AM control plants, with greater yield, harvest indices, and grain P, Zn and Fe contents. During the early growth stages, AM colonisation led to temporary growth depressions. There were also AM fungal and P fertilisation effects on sorghum time‐of‐flowering. The sorghum genotype with the highest AM colonisation could barely produce grain when non‐inoculated. The two genotypes that failed to mature had very low AM colonisation. Generally, the genetically diverse sorghum genotypes were highly responsive to AM colonisation and produced more grain of greater nutritive quality when colonised, without adverse consequences for micronutrient bioavailability. Abstract : Sorghum is an important cereal crop that provides calories and nutrients for much of the world's population, and it is often grown with low fertiliser input. Optimising the yield and nutritive content and bioavailability of sorghum grain with minimal input is of importance for human nutrition, and arbuscular mycorrhizal (AM) fungi have previously shown potential to assist in this. Across sorghum genetic diversity, AM fungi improved the yield, nutrition and zinc and iron bioavailability of grain in a low phosphorus soil. Thus, food production systems that effectively manage AM fungi may improve consumer outcomes.